Short tandem repeats on X and Y chromosomes in relation to prostate cancer risks in Saudi male population - Albujja, Mohammed Harb Khalil (2020)
Prediction of the susceptible population to any hereditary disease is one of the main tracks of human genetics. Although there were studies related between prostate cancer (PrCa) and family hereditary or Y-chromosome alleles frequencies and other studies related between X-chromosome alleles frequency and PrCa, most of them were inconclusive because of the limited number of biomarkers and/or samples as well as the investigation of sex chromosomes markers separately. Forensic short tandem repeats (STRs) are sometimes best to seek information from lineage markers to aid with specific inheritance scenarios. Therefore, many studies were conducted to establish an association between phenotype and genotype in that disease by Y STR lineages. Lineage markers including Y and X-chromosomes markers can aid kinship analysis. Therefore, in the current study it was hypothesized that the analyses of both X and Y-chromosomes together besides increasing the number of investigated markers to 35 markers (23 in Y-chromosome and 12 in X-chromosome) will give comprehensive linkage information between sex chromosomes and PrCa. Most of the previous studies compare PrCa patients only and healthy controls. Also, they examine the genetic biomarkers on Y-chromosome only. While the current study included PCa and benign prostate hyperplasia (BPH) patients as well as examined the biomarkers on X and Y-chromosomes. Multiple comparisons were done, three of them between (malignant, benign, and malignant plus benign patients), respectively, and healthy controls group. One more comparison was established between benign and malignant patients. This research was carried to fill a gap in research by the identification of a genetic biomarker able to predict men’s susceptibility to malignant or benign disease. To the best of our knowledge, this study is the ﬁrst to analyze 23 DYS loci in PrCa in a Saudi male population and the first to analyze 12 DXS loci in PrCa patients in a Saudi male population, and worldwide. To perform this study, 248 subjects were recruited, comprising 92 patients and 156 healthy controls. All DNA samples were amplified using PowerPlex® Y23 System and Investigator® Argus X-12 QS. The fragments analysis for alleles of 23 DYS and 12 DXS loci were performed using Genetic Analyzer.